(untitled) (Olhares, 2015)
The actor’s education and the methodological process used by the Russian Academy of Art – GITIS, one of the oldest theater schools in the world, located in Moscow. In the same time that the text emphasizes the artistic and pedagogical basis for the actor’s education, it also draws an historical, political, social and economic comparison with Russian panorama currently.